Emerging Trends for Microbiome Analysis: From Single-Cell Functional Imaging to Microbiome Big Data. (February 2017) - Xu, Jian; Ma, Bo; Su, Xiaoquan; Huang, Shi; Xu, Xin; Zhou, Xuedong; Huang, Wei E.; Knight, Rob
Abstract: Method development has always been and will continue to be a core driving force of microbiome science. In this perspective, we argue that in the next decade, method development in microbiome analysis will be driven by three key changes in both ways of thinking and technological platforms: ① a shift from dissecting microbiota structure by sequencing to tracking microbiota state, function, and intercellular interaction via imaging; ② a shift from interrogating a consortium or population of cells to probing individual cells; and ③ a shift from microbiome data analysis to microbiome data science. Some of the recent method-development efforts by Chinese microbiome scientists and their international collaborators that underlie these technological trends are highlighted here. It is our belief that the China Microbiome Initiative has the opportunity to deliver outstanding "Made-in-China" tools to the international research community, by building an ambitious, competitive, and collaborative program at the forefront of method development for microbiome science.